The effect of using the Balanced Scorecard (BSC) on reducing the financial and administrative corruption in Iraqi Government Units - Saoud Jayed Mashkour Alamry; Hayder Abbas Al-Attar; Abdulhadi Salman Salih (Goodwood Publishing, 2022)
Purpose: This research aims to explore the importance application the Balanced Scorecard (BSC) to the accountants and auditors in government units, which in turn contributes to raising the efficiency of scientific and practical performance as one of the fights against financial and administrative corruption suffered by the majority of the government units in Iraq. Research methodology: This research used a statistical method in the analysis and measurement by using (SPSS) program to extract the necessary statistical indicators to determine the impact of the independent variables (BSC) on the dependent variable (financial and administrative corruption). Results: There is a significant correlation between the Balanced Scorecard (BSC) and the professional performance efficiency of accountants and auditors, as well as a significant correlation between the Balanced Scorecard (BSC) and the fight against financial and administrative corruption. Conclusion: The study finds that the Balanced Scorecard (BSC) improves performance and helps combat corruption in government units. However, challenges like legislative conflicts and lack of transparency hinder its implementation. The study recommends training and workshops to better apply BSC and address corruption in Samawah, Iraq. Limitations: There is a conflict between legislation, laws, and administrative controls in some measures of the balanced scorecard. Contributions: Find recommended the need to apply the balanced scorecard in the evaluation of the efficiency and improve the performance of the work of accountants and auditors, and the need for government units in the city of Samawah-Iraq.